2012
DOI: 10.1111/j.1468-3083.2012.04480.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of livedoid vasculopathy with alprostadil (PGE‐1): case report and review of published literature

Abstract: EditorThe diagnosis and treatment of livedoid vasculopathy is a challenge to the clinician. 1 A 47-year-old patient presented with livid reticular discoloration and ulceration on both legs, aggravated by exposure to cold since the age of 26 years. Clinical examination revealed painful focal purpuric ulcerating lesions, atrophic scarring, teleangiectasia, hemosiderin deposits and hyperpigmentation (Fig. 1a). Laboratory parameters such as coagulation factors, phospholipid antibodies, ANA, ENA, ANCA, C3, C4, immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Application of low molecular heparins as non‐licensed treatment option is regularly used, but modern anticoagulants as well demonstrated effectiveness in recently performed clinical trials . In addition, vasodilators like prostaglandins might be successfully used for treatment of LV to promote healing of ulcerations . According to the literature, women are more often affected with a ratio of women:men up to 3:1 .…”
Section: Introductionmentioning
confidence: 99%
“…Application of low molecular heparins as non‐licensed treatment option is regularly used, but modern anticoagulants as well demonstrated effectiveness in recently performed clinical trials . In addition, vasodilators like prostaglandins might be successfully used for treatment of LV to promote healing of ulcerations . According to the literature, women are more often affected with a ratio of women:men up to 3:1 .…”
Section: Introductionmentioning
confidence: 99%
“…This is a case of a patient with TEC with unilateral sparing of an axilla that had previously been exposed to radiation therapy and ALND. 4 Though this patient reported little baseline sweating, and therefore did not note hypohidrosis in the left axilla, decreased sweat production in the distribution of the intercostobrachial nerve is a complication of mastectomy and ALND. Sparing of an area of sympathetic denervation in this patient supports the theory that TEC is caused by excretion of chemotherapeutic agents in sweat.…”
Section: Unilateral Axillary Toxic Erythema Of Chemotherapy In a Patimentioning
confidence: 70%
“…Mittag et al 3 reported the first case of SS treated with iloprost in cycles also obtaining a remission in pain and clearing of the skin ulcers. Mofarrah et al 4 described a case of livedoid vasculitis successfully treated with PGE-1 at dose of 60 μg for 5 days followed by a dose of 60 μg of monthly maintenance. The pain disappeared in the first 2 days, and ulcers healed after 3 weeks of treatment.…”
Section: Treatment Of Skin Ulcers Secondary To Sneddon Syndrome With mentioning
confidence: 99%
See 1 more Smart Citation
“…Prostaglandin E1 (PGE 1 ) has protective effects against acute and chronic ischemia in various organs (9)(10)(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%